66‐3: The Way to Improve Black Circle Mura in Curved Display by Polyimide‐less Technology. Issue 1 (25th September 2020) - Cui, Wei; Lan, Song; Tseng, Te-Jen; Hsieh, Chung-Ching
Abstract : In the fabrication of curved diplay, there always exist black circle mura, which is induced by the curvature. To improve this phenomenon, polyimide‐less technology was introduced. Polyimide‐less technology is a technology in which an additive can replace polyimide film to align LC molecules. In this technology, the additive added in liquid crystal (LC) host can not only align the LC molecules, but also have different pretilt angle generation ratio compared with PI film. In this paper, we fabricated curved panels using CF substrate with PI and TFT substrate without PI.The additive in PI‐less liquid crystals could anchor the TFT substrate and align the LC molecules on the TFT side. After UV process, the CF substrate had smaller pretilt angle. And the black circle mura appeared in the curved panel could be solved completely. Then we also studied the alignment, optical and image sticking performance, there existed no difference between the curved panels using PI‐less technology and the curved ones with normal PI layers.